FDD LTE Performance Simulation Based on Massive Antenna Array. (4th July 2022) - Wang, Jun; Mu, Dejun
Abstract : There are two methodologies to realize 3D MIMO for FDD LTE, MU-MIMO-based virtual beam (VB), and four-cell soft-split cell (SSC), which beamforms four logical cells in one physical sector, and this paper is aimed at figuring out which brings more performance between VB and SSC. In the first place, brief introduction for the mechanism of VB and SSC are presented. Subsequently, detailed systematic simulations based on WINNER II are carried out based on different traffic models (low load, medium load, and high load) and user distribution is also considered. For accurate evaluation on the performance gain of VB and SSC, 4T4R solution is also simulated as the benchmark, which is widely deployed to improve the capacity of FDD LTE by operators. Based on the simulation of results of the subsequent KPIs, cell throughput, average cell throughput, average UE throughput, and average layer number, VB and SSC effectively increase single-cell capacity and user experience in high load scenario compared with 4T3S solution and VB can bring more gain.